Elastic Compressive Stockings in the Prevention of Postthrombotic Syndrome: Is the Evidence so Clear? - Flora, Andreia; Silva, Ana Celeste; Madeira, Ana Rodrigues; Tainha, Sara (Gazeta Médica, 2023)
Postthrombotic syndrome (PTS) is a late complication of deep vein syndrome (DVT) that occurs in 20%-50% of patients. Its symptoms are the cause of great morbidity and compromise the quality of life of patients. Therefore, prevention of PTS after an episode of DVT is critical. Several guidelines recommend wearing compression stockings daily as a way to prevent PTS. However, the SOX essay concluded that there is no benefit in using compression therapy, and changed the paradigm of using compression stockings to prevent PTS. Since then, and considering that using compression stockings also presents disadvantages such as price and discomfort, several studies have been carried out in this area. The main objective of this review is to determine the efficiency of using elastic compression stockings in the prevention of PTS. Of the 16 articles obtained from the different databases, 8 were included in the narrative review. International guidelines on this topic were also included, namely the European Society for Vascular Surgery (ESVS) 2021 Clinical Practice Guidelines on the Management of Venous Thrombosis. The majority of studies demonstrated non-reduction of the incidence of PTS with compression therapy, while others continue to suggest benefits with its use. The studies present contradictory evidence regarding the use of compression stockings in PTS prophylaxis. One limitation of this review is due to the heterogeneity of the studies. New studies with better quality methods, larger samples, and using consistent methodologies are needed in order to conclude if there is any benefit of using compression stockings to prevent PTS.